Immersive Virtual Reality Field Trips Facilitate Learning About Climate Change - Markowitz, David M.; Laha, Rob; Perone, Brian P.; Pea, Roy D.; Bailenson, Jeremy N. (Frontiers in Psychology, 2018)
Across four studies, two controlled lab experiments and two field studies, we tested the efficacy of immersive Virtual Reality (VR) as an education medium for teaching the consequences of climate change, particularly ocean acidification. Over 270 participants from four different learning settings experienced an immersive underwater world designed to show the process and effects of rising sea water acidity. In our studies, people learned about marine science and displayed more positive attitudes toward the environment after a coral- versus self-avatar manipulation. The analyses also revealed a potential post-hoc mechanism for the learning effects, as the more that people explored the spatial learning environment, the more they demonstrated a change in knowledge about ocean acidification. This work is unique by showing distinct learning gains or an interest in learning across a variety of participants (high school, college students, adults), measures (learning gain scores, tracking data about movement in the virtual world, qualitative responses from classroom teachers), and content (multiple versions varying in length and content about climate change were tested). Our findings explicate the opportunity to use immersive VR for environmental education and to drive information-seeking about important social issues such as climate change.